Reflections on Edward Said’s Legacy: Orientalism, Cosmopolitanism, and Enlightenment - Yu, Henry (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2006)
AbstractHow are we to understand Edward Said's critique of the imbrication of knowledge and colonial power in light of his own education at elite universities such as Princeton and Harvard? Is Said's own path through elite colonial schooling in the Middle East and the exclusive schools of the United States a context for understanding the origins of his arguments in Orientalism? Yu uses the tension in Said's own commitment to a cosmopolitan ideal of knowledge to explore the contradictions within the legacies of the Enlightenment and European colonialism.